Contextual Teaching and Learning-Based Physics Module: An Effective Approach to Improve Scientific Literacy - Nova Wardani; Abdul Salam; Sarah Miriam (Universitas Lambung Mangkurat, 2026)
The low level of scientific literacy among Indonesian students results in their limited ability to identify scientific explanations of phenomena and to accurately relate data to conclusions. In response to this issue, the present study aims to evaluate the effectiveness of a physics teaching module based on Contextual Teaching and Learning (CTL) in improving students’ scientific literacy. This pre-experimental study employed a one-group pretest–posttest design. The research subjects consisted of 30 twelfth-grade students from a public senior high school in Banjarmasin. Data were collected using a scientific literacy achievement test administered before and after the implementation of the teaching module, and subsequently analyzed using the N-gain calculation. The results of the study indicate that the developed physics teaching module demonstrated medium effectiveness, with an N-gain score of 0.52. It can therefore be concluded that the physics teaching module based on the CTL approach is effective for classroom use in improving students’ scientific literacy. These findings suggest that integrating the CTL approach into teaching module can serve as an alternative to support the improvement of scientific literacy among senior high school students.